Exploring entrepreneurial orientation dimensions in the property business: A scale development - Rodvinit, Chayakon; Tangpinyoputtikhun, Yanin (Edelweiss Applied Science and Technology, 2024)
This study investigates the dimensions of entrepreneurial orientation (ENO) within the context of property business. A survey was conducted with 355 respondents to explore various dimensions of EO, including innovation, resilience quality, organisational culture, entrepreneurial capability, innovative marketing strategy, customer care, scalability, and effort. Results showed that the majority of respondents were male (54.90%) and belonged to Generation X (68.20%), with a significant portion from the Upper Northeast zone (53.50%). The study employed Principal Axis Factoring (PAF) with Promax rotation to identify EO dimensions, resulting in eight unique factors explaining 60.8% of the variance. These dimensions included Innovation Technology, Resilience Quality, Organizational Culture, Entrepreneurial Capability, Innovative Marketing Strategy, Customer Care, Scalability, and Effort. The study also conducted a Confirmatory Factor Analysis (CFA), confirming the reliability and validity of the proposed model. The calculated Average Variance Extracted (AVE) and composite reliability values met the convergent and discriminant validity criteria. Overall, this research contributes to a deeper understanding of EO in the property sector and provides insights for property businesses and policymakers to foster entrepreneurial behaviour and drive performance.